Teaching moves and strategies of physics teacher in Manila Public Secondary Schools - Alcid, Luzita L. (1978)
The study aimed to determine the different moves and strategies used by Physics teachers in Manila to present a concept. Thirty Manila public school teachers were chosen through systematic sampling, undertaking the study during the first semester of SY 1977-1978. Each move was categorized using Henderson's model, and the strategy categorized into two. The chi square test was applied to determine the relationship of the teacher variables and the strategy choice. Results have shown that teachers used apperception, motivation, presentation, abstraction, interpretation, and application in introducing a concept. The heuristic strategy was also more frequently used than the expository strategy. There is no relationship between the choice of moves and the academic degree completed as well as with the number of years of teaching Physics. However, there is a significant relationship between the number of Physics units earned and the choice of moves.
Thesis (M.A.T. Physics)--University of the Philippines, Diliman.
Keywords: Physics teachers -- In-service training -- Philippines -- Manila; Physics -- Study and teaching (Secondary) -- Philippines -- Manila; Public school teachers -- In-service training -- Philippines -- Manila